STODS: the Swedish Twin project Of Disability pension and Sickness absence - Svedberg, Pia; Narusyte, Jurgita (Karolinska Institutet, 2018)
STODS was started in 2008, aiming to investigate risk factors and consequences of sickness absence and disability pensions. Special focus is on musculoskeletal and mental diagnoses, which accounts for approximately 70% of all sickness absence. By combining twin methodology and sickness insurance research methods, a unique possibility is given to adjust for and examine genetic and environmental factors of importance for sickness absence and disability pension.

Several studies have been conducted, others are in progress. The project are collaborating with researchers in Helsinki and Olso where similar work on disability pension is carried out. A network including also Denmark and Norway was established during 2012 (NorTwinDiSA), focusing on sickness absence research using Nordic twin settings.

Purpose:

The overall objective of the STODS (Swedish Twin project of Disability pension and Sickness absence) is to investigate the importance of genetic and environmental/psychosocial factors for sickness absence and for disability pension in a nationwide, population-based twin sample.

STODS startade 2008 med syfte att studera riskfaktorer för att bli, respektive konsekvenser av att vara, sjukskriven, i sjuk- eller aktivitetsersättning. Särskilt fokus är på rörelseorganens sjukdomar och psykiska diagnoser, vilka står för ca 70 % av sjukskrivningarna. Genom att kombinera forskningsmetodik om tvillingar med sjukfrånvaroforskning ges en unik möjlighet att kontrollera för och att undersöka ärftliga faktorers betydelse för sjukskrivning, sjuk- eller aktivitetsersättning, liksom konsekvenser av detta, kunskap som ofta efterfrågas inom sjukfrånvaroforskningen.

Flera olika delstudier har genomförts, andra pågår. Projektet samarbetar sedan flera år med forskargrupper i Helsingfors och Oslo som bedriver liknande studier. Sedan 2012 har ett nordiskt nätverk etablerats (NorTwinDiSa), kring sjukfrånvarostudier baserade på de nordiska tvillingkohorterna, där även Danmark ingår.

Syfte:

I projektet STODS är syftet att få ökad och mer detaljerad kunskap om riskfaktorer för att bli sjukskriven eller för att få sjuk- eller aktivitetsersättning, samt om eventuella konsekvenser av att vara sjukskriven eller ha sjuk- eller aktivitetsersättning.
STODS: the Swedish Twin project Of Disability pension and Sickness absence
Keywords: mental health; psykisk hälsa; Mental Disorders; Psykiska störningar; Risk Factors; Riskfaktorer; Workload; Arbetsbelastning; Environment; Miljö; Environmental Exposure; Miljöexponering; Sick Leave; Sjukfrånvaro; Morbidity; Sjuklighet; Stress, Psychological; Psykologisk stress; Heredity; Ärftlighet; working conditions; arbetsförhållanden; Twins; Tvillingar; Twins, Dizygotic; Tvåäggstvillingar; Twins, Monozygotic; Enäggstvillingar; national register; nationellt register; REWHARD; REWHARD; muskuloskeletal system; rörelseorgan; disability pension; sjukersättning; mental diagnoses; psykiska diagnoser; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap; Health Sciences; Hälsovetenskap; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin